Grenzen der Personalisierung des Rechts - Bender, Philip Maximilian (Mohr Siebeck, 2023)
New technologies such as Big Data have the potential to personalize legal norms. However, the data-based personalization of law comes with significant risks. Taken to its extreme, it would threaten the foundations of liberal society and lead to a system of micro-socialism.
PublicationDate: 20231130
Keywords: Liberalismus -- Verhaltensökonomik -- Big Data -- Geheimdienste -- Prozesszweck -- richterliche Hinweispflicht -- Algorithmen -- Willenstheorie -- Law xxxAMPRxxx Technology -- Jüdische Weisheitsliteratur -- Rechtsphilosophie -- Rechtstheorie -- Verfassungsrecht und Staatslehre -- Bürgerliches Recht